2010
DOI: 10.1007/s11547-010-0490-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between multislice CT and MR imaging in the diagnostic evaluation of patients with pancreatic masses

Abstract: MRI represents a valid diagnostic alternative to CT in the evaluation of patients with pancreatic masses, both for correct identification and characterisation of primary lesions and to establish resectability in the case of malignancies. New high-field MRI equipment allows optimal imaging quality with good contrast resolution in evaluating the upper abdomen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 25 publications
3
32
0
1
Order By: Relevance
“…In this study, MDCTA was found to have a sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of 100%, 71%, 85%, 100%, and 89%, respectively, which was similar to the results reported by Fusari et al 26 and Zamboni et al 48 Results vary according to the various generations of MDCT scanners used.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…In this study, MDCTA was found to have a sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of 100%, 71%, 85%, 100%, and 89%, respectively, which was similar to the results reported by Fusari et al 26 and Zamboni et al 48 Results vary according to the various generations of MDCT scanners used.…”
supporting
confidence: 88%
“…17 The sensitivity of CT in the detection of pancreatic tumors has improved in recent times and lies between 75% and 100% in different series, with a specificity of 70%-100%. [22][23][24][25][26][27][28][29] However, the smaller the tumor is, the less the CT sensitivity. It is reported that CT sensitivity for lesions measuring #2 cm is between 68% and 77% 23,25 and the accuracy close to 77%.…”
Section: Accuracy Of Mdctmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusari c соавт. в своем исследова-нии обнаружили, что чувствительность, специ-фичность, точность, положительная прогности-ческая ценность и отрицательное предсказа-тельное значение для МРХПГ рака поджелудоч-ной железы составляют 100%, 88%, 98%, 97% и 100% соответственно [60]. Они также обнару-жили, что МРХПГ для оценки резектабельности карцином поджелудочной железы обладает чув-ствительностью, специфичностью, точностью, положительной прогностической ценностью и отрицательной прогностической значимостью 88%, 100%, 90%, 100% и 70% соответственно.…”
Section: методы диагностикиunclassified
“…Multidetector computed tomography (MDCT) and angiography scans and magnetic resonance imaging (MRI) along with magnetic resonance cholangiopancreatography (MRCP) have been demonstrated to provide the highest accuracy in terms of non-invasive imaging modalities to diagnose, stage and determine the vascular involvement by pancreatic carcinomas of the head (>3 cm) [12][13][14][15], body and tail [16].…”
Section: Radiologymentioning
confidence: 99%